An Alkaline Protease from Bacillus pumilus MP 27: Functional Analysis of Its Binding Model toward Its Applications As Detergent Additive - Baweja, Mehak; Tiwari, Rameshwar; Singh, Puneet K.; Nain, Lata; Shukla, Pratyoosh (Frontiers in Microbiology, 2016)
A proteolytic strain of Bacillus pumilus MP 27 was isolated from water samples of Southern ocean produced alkaline protease. Since protease production need expensive ingredients, an economically viable process was developed by using low cost carbon source, wheat straw, supplemented with peptone. This protease was active within temperature ranges 10˚C -70˚C at pH 9. This process was optimized by response surface methodology using a Box Bekhman design by Design Expert 7.0 software that increased the protease activity to 776.5 U/ml. Moreover, the enzyme was extremely stable at a broad range of temperature and pH retaining 69% of its activity at 50 ºC and 70% at pH 11. The enzyme exhibited excellent compatibility with surfactants and commercial detergents, showing 87% stability with triton X-100 and ̴ 100% stability with Tide commercial detergent. The results of the wash performance analysis demonstrated considerably good de-staining at 50ºC and 4ºC with low supplementation (109 U/ml). Molecular modeling of the protease revealed the presence of serine proteases, subtilase family and serine active site and further docking supported the association of catalytic site with the various substrates. Certainly, such protease can be considered as a good detergent additive in detergent industry with a possibility to remove the stains effectively even in a cold wash.